Dental resin mixture, dental resin and preparation method thereof, color difference uniformity evaluation method and dental restoration
By using 0.1 ~ 6 μm of inorganic particles and a specific proportional polymerization monomer in the dental resin mixture, and using specific mixing and processing steps, the problem of uneven color distribution in dental resin materials has been solved, and a better thing is achieved. Mechanical performance and aesthetics.
Patent Information
- Application Number
- CN202411301731.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-21
AI Technical Summary
During the manufacturing process of existing resin materials for dental cutting processing, inorganic particles in the mixture are prone to precipitation, resulting in uneven color distribution and affecting the aesthetics and mechanical properties of the material.
A dental resin mixture is provided, including inorganic particles of 0.1 to 6 μm, a polymerizable monomer with a mass ratio of (1 to 4): (6 to 10), and an appropriate amount of initiator. Through specific mixing and processing steps, it ensures The inorganic particles are evenly dispersed and the color distribution is uniform.
The color distribution uniformity and mechanical properties of dental resin are realized, and the aesthetics and long -term stability of dental repair are ensured.
Smart Images

Figure CN119326668A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of dental resins, and in particular to a dental resin mixture, a dental resin and a preparation method thereof, a color difference uniformity evaluation method, and a dental restoration. Background Art
[0002] With the rapid development of computer-aided design / computer-aided manufacturing (CAD / CAM) technology, people have put forward higher and higher requirements on the speed and performance of tooth restoration. At present, there are two main types of machinable dental restoration materials that are compatible with the CAD / CAM technology system, namely ceramic materials and resin restoration materials. Both materials have their own advantages and disadvantages in dental restoration. Ceramic materials have high mechanical properties and aesthetic properties, but due to their brittleness and high wear resistance, they cause great damage to natural teeth. Resin materials are widely used in CAD / CAM technology due to their advantages such as low price, good toughness, easy machining, short restoration cycle, and no wear on the opposing teeth.
[0003] In the manufacturing process of existing dental cutting resin materials, inorganic particles in the mixture are easy to precipitate, and the resin monomer is a viscous liquid. During the production process, the monomer part is easy to mix unevenly with the inorganic particles and the pigment composition part, resulting in uneven color distribution. This not only affects the aesthetics of the material, but also may affect the mechanical properties of the resin material such as bending strength and hardness, and have an adverse effect on the effect of dental restoration.
[0004] Therefore, developing a dental cutting resin material with uniform color distribution is a technical problem that those skilled in the art need to solve urgently. Summary of the invention
[0005] The object of the present invention is to provide a dental resin mixture, a dental resin and a preparation method thereof, a color difference uniformity evaluation method, and a dental restoration, so as to obtain a dental resin and a dental restoration with smaller color difference between local areas, better overall color uniformity of the product and optional mechanical properties.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A dental resin mixture, comprising:
[0008] Inorganic particles, polymerizable monomers and initiators;
[0009] The particle size of the inorganic particles is 0.1 to 6 μm, preferably 0.5 to 5 μm, and the polymerizable monomer comprises triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of (1 to 4): (6 to 10), preferably (2 to 4): (6 to 9).
[0010] In some embodiments of the present invention, the inorganic particles are 80 to 88 parts by weight, preferably 80 to 85 parts by weight, the polymerizable monomer is 12 to 20 parts by weight, preferably 15 to 20 parts by weight, and the initiator is 0.0001 to 0.002 parts by weight, preferably 0.0003 to 0.0016 parts by weight.
[0011] In some embodiments of the present invention, the inorganic particles are selected from at least one of glass, glass ceramics, quartz, fused quartz, silica gel, silicon, alumina, diatomaceous earth, kaolin, clay minerals, activated soil, natural zeolite, synthetic zeolite, mica, silicon dioxide, calcium fluoride, ytterbium fluoride, calcium phosphate, barium sulfate, zirconium oxide, titanium dioxide, hydroxyapatite and inorganic fillers containing heavy metal elements;
[0012] Preferably, the glass or glass ceramic comprises silicon dioxide as a main component and contains at least one of boron, aluminum or heavy metal elements;
[0013] Preferably, the heavy metal element is selected from at least one of zirconium, barium, titanium, lanthanum or strontium;
[0014] Preferably, the clay mineral is montmorillonite;
[0015] Preferably, the inorganic particles are barium glass powder, more preferably silanized barium glass powder.
[0016] In some embodiments of the present invention, the dental resin mixture further comprises a colorant;
[0017] The colorant is selected from at least one of organic pigments and inorganic pigments;
[0018] Preferably, the inorganic pigment is an oxide pigment, more preferably at least one selected from red iron oxide, yellow iron oxide, black iron oxide, and titanium dioxide;
[0019] Preferably, the colorant is 0 to 1 part by weight, preferably 0.005 to 0.5 part by weight, based on 100 parts by weight of the sum of the inorganic particles, polymerizable monomers, initiators and colorants in the dental resin mixture.
[0020] In some embodiments of the present invention, the polymerizable monomer further comprises at least one of bisphenol A propylene glycol dimethacrylate, ethoxy bisphenol A diacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, triethylene glycol dimethacrylate, triethylene glycol dimethacrylate, methacrylate, polyurethane diacrylate, 2-hydroxyethyl acrylate, and 2-hydroxyethyl methacrylate. In the context of the present invention, polymerizable monomers are also referred to as resin monomers or acrylic monomers.
[0021] In some embodiments of the present invention,
[0022] Preferably, the total amount of triethylene glycol dimethacrylate and urethane dimethacrylate accounts for at least 50% by weight, preferably at least 80% by weight of the total amount of polymerizable monomers;
[0023] Preferably, the polymerizable monomer comprises triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of 3:7.
[0024] In some embodiments of the present invention, the initiator is a peroxide and / or an azo compound. Preferably, the initiator is benzoyl peroxide.
[0025] In some embodiments of the present invention, the dental resin mixture further comprises a solvent;
[0026] The solvent is preferably selected from ethanol, anhydrous ethanol, methanol, propanol, n-propanol, isopropanol, butanol, n-butanol, tert-butanol, isobutanol, pentanol, hexanol, ethylene glycol, propylene glycol, butylene glycol, glycerol, trimethylolpropane, ethyl acetate, methyl acetate, dimethylformamide, ether, acetone, methyl ethyl ketone, heptane, more preferably anhydrous ethanol.
[0027] In order to achieve the above object, the present invention also provides the following technical solutions:
[0028] A dental resin, the raw material of which is the dental resin mixture.
[0029] In order to achieve the above object, the present invention also provides the following technical solutions:
[0030] A method for preparing a dental resin, the method comprising the following steps:
[0031] S1, mixing inorganic particles, polymerizable monomers, initiators, solvents and optional colorants;
[0032] S2, drying, grinding, and sieving the mixture obtained in step S1 to obtain a powdery mixture;
[0033] S3, dry-pressing the powdery mixture obtained in step S2 to obtain a block body;
[0034] S4, heating and pressurizing the block body obtained in step S3 to harden it, and obtaining the dental resin after cooling.
[0035] In some embodiments of the present invention, in step S1, the mixing is performed using a ball mill;
[0036] Preferably, the ball mill jar of the ball mill is made of any one of zirconium oxide, polyurethane, nylon and polyethylene;
[0037] Preferably, the grinding balls in the ball mill are made of agate or zirconium oxide;
[0038] Preferably, the rotation speed of the ball mill is 600-800 rpm, and the ball milling time is 0.5-1.5 h;
[0039] Preferably, a solvent, preferably anhydrous ethanol, is added before ball milling.
[0040] In some embodiments of the present invention, in step S2, the drying is performed in a drying oven, the drying temperature is 45 to 65° C., and the drying time is 4 to 12 hours;
[0041] Using a sieve to perform the screening;
[0042] Preferably, the screen is a synthetic fiber screen or a polyurethane screen;
[0043] Preferably, the size of the sieve is 12 to 24 meshes.
[0044] In some embodiments of the present invention, in step S3, the pressure of the dry pressing is 6-15 MPa.
[0045] In some embodiments of the present invention, in the step S4, the block green body is heated and pressurized at a temperature of 90 to 160° C. and a pressure of 120 to 180 MPa for 5 to 8 hours, and then cooled to obtain the dental resin.
[0046] In order to achieve the above object, the present invention also provides the following technical solutions:
[0047] A method for evaluating the color difference uniformity of the above-mentioned dental resin, the evaluation method comprising the following steps:
[0048] A1, taking at least two samples on the dental resin, using a spectrophotometer, and measuring the L value, a value, and b value of the samples according to the CIELAB color space model corresponding to ISO11664-4,
[0049] Each sample is numbered from 1 to n, where n is an integer greater than or equal to 2. Sample No. 1 measures L1, a1, and b1, and sample No. n measures L n 、a n and b n ;
[0050] A2, substitute the L value, a value, and b value data obtained in step A1 into the formula ΔE (i,j) =[(ΔL (i,j) ) 2 +(Δa (i,j) ) 2 +(Δb (i,j) ) 2 ] 1 / 2The calculation is performed in which ΔL (i,j) , Δa (i,j) , Δb (i,j) It is the difference between the CIE L, a, and b values of any two samples, that is, ΔL (i,j) =|L i -L j |, Δa (i,j) =|a i -a j |,Δb (i,j) =|b i -b j |, i and j are both integers greater than 0 and not greater than n, i≠j, i represents sample number i, j represents sample number j, ΔE (i,j) Represents the color difference between any two samples.
[0051] Among them, if for any set of i and j, there is ΔE (i,j) ≤1.2, the color distribution of the dental resin is considered to be uniform.
[0052] In some embodiments of the present invention, in step A1, the center position of the surface of the dental resin is used as the origin to divide the quadrants into four equal parts, and at least one sample is sampled in each quadrant, n≥4. Preferably, one sample is oriented in each quadrant, n=4.
[0053] In some embodiments of the present invention, the size of the sample is (1-10)×(1-10)×(1-2) mm.
[0054] In order to achieve the above object, the present invention also provides the following technical solutions:
[0055] A dental restoration, wherein the dental restoration is any one of an inlay, an onlay, a crown, a bridge, a veneer, and an implant superstructure;
[0056] The dental restoration is obtained by cutting with a CAD / CAM device using the dental resin mixture or the dental resin obtained by the preparation method.
[0057] Further areas of applicability will become apparent from the description provided in the present disclosure.
[0058] The description and specific examples in this summary are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure.
[0059] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0060] 1. The present invention provides a dental resin with small color difference between local areas and better overall color uniformity of the product, and a preparation method for the dental resin;
[0061] 2. The present invention provides a dental resin with better mechanical properties such as bending strength and hardness.
[0062] 3. The present invention provides an evaluation method for evaluating the color difference uniformity of dental resin, which can be used to evaluate the color difference uniformity of dental resin and determine whether the color of dental resin is sufficiently uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some implementation plans of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0064] Figure 1 A flowchart of a method for preparing a dental resin provided in one embodiment of the present invention;
[0065] Figure 2 This is a flowchart of a method for evaluating color uniformity of dental resin provided in another embodiment of the present invention. DETAILED DESCRIPTION
[0066] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present invention. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0067] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values close to the exact value, such as all possible numerical values within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values of the range, the endpoint values and the specific point values in the range, and the specific point values can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.
[0068] The terms used in the present disclosure are only intended to describe specific exemplary embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "a kind of" and "the" as used in the present disclosure may be intended to also include plural forms. The terms "comprise", "include", "contain" and "have" are inclusive, thus illustrating the presence of the features, elements, compositions, steps, integers, operations and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or their collections. Although the open term "comprise" should be understood as a non-limiting term for describing and claiming the various embodiments described in the present disclosure, in some aspects, the term may be alternatively understood as a more restrictive and limited term, such as "consisting of..." or "consisting essentially of..." Thus, for any given embodiment of a narration composition, material, component, element, feature, integer, operation and / or process step, the present disclosure also particularly includes an embodiment consisting of or essentially consisting of such a composition, material, component, element, feature, integer, operation and / or process step. In the case of “consisting of,” alternative embodiments exclude any additional compositions, materials, components, elements, features, integers, operations and / or process steps, while in the case of “consisting essentially of,” any additional compositions, materials, components, elements, features, integers, operations and / or process steps that materially affect the basic and novel characteristics are excluded from such embodiments, but any compositions, materials, components, elements, features, integers, operations and / or process steps that do not materially affect the basic and novel characteristics may be included in the embodiments.
[0069] Any method steps, processes, and operations described in the present disclosure should not be construed as necessarily requiring their performance in the particular order discussed or illustrated, unless expressly identified as a certain order of performance. It should also be understood that additional or alternative steps may be used unless otherwise stated.
[0070] In this application, except for the contents explicitly described, any matters or items not mentioned are directly applicable to those known in the art without any changes. Moreover, any embodiment described in this disclosure can be freely combined with one or more other embodiments described in this disclosure, and the technical solutions or technical ideas formed thereby are regarded as part of the original disclosure or original record of this application, and should not be regarded as new contents that have not been disclosed or anticipated in this disclosure, unless a person skilled in the art considers that the combination is obviously unreasonable.
[0071] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.
[0072] Unless otherwise stated, when % is mentioned herein, it means wt. %.
[0073] First aspect
[0074] The invention provides a dental resin mixture, which comprises inorganic particles, polymerizable monomers and an initiator.
[0075] In some embodiments of the present invention, the particle size of the inorganic particles is 0.1 to 6 μm, preferably 0.5 to 5 μm. Exemplarily, the particle size of the inorganic particles can be any one of 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, or any one of the values in the range between any two of the above values. The inorganic particles in this particle size range can scatter light more evenly. When light enters the dental resin material, these particles can make the light propagate and scatter in a more consistent manner inside the material, avoiding strong light reflection or absorption differences in local areas, thereby reducing the generation of color difference. The particles in this particle size range can ensure that the absorption of light is relatively consistent to a certain extent, and the overall color of the material will not deviate due to excessive absorption of light of a specific wavelength by some particles. The inorganic particles in this particle size range have better compatibility with dental resin. They can be dispersed more evenly in the resin matrix without particle aggregation or uneven distribution. This will make the color more uniform in the cured resin without color differences caused by local high or low particle concentrations. Inorganic particles of this size can form a stable physical structure in the resin and are not prone to displacement or reaggregation during use, which helps maintain the long-term stability of the material's color.
[0076] In some embodiments of the present invention, the polymerizable monomer comprises triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of (1-4): (6-10), preferably (2-4): (6-9). The chemical structures of these two substances do not contain unstable chromophores that are prone to color change. During the polymerization process and subsequent use, new chromophores will not be generated due to structural changes, thereby ensuring the stability of the material color and reducing the generation of color difference. After curing, these two substances can form a polymer network with a relatively uniform refractive index. When light passes through the dental resin material, due to the uniformity of the refractive index, there will be no excessive difference in local light refraction, avoiding color differences caused by uneven refraction, making the overall color of the material more uniform. Triethylene glycol dimethacrylate and urethane dimethacrylate have good compatibility with other ingredients (such as inorganic particles, initiators, etc.). During the polymerization reaction, they can be evenly mixed with other components to ensure the uniformity of the entire system. This uniform mixing state helps to form a polymer with uniform color and reduce color differences caused by uneven distribution of components. The polymerization reaction of these two substances is relatively controllable, and the polymerization rate and degree can be adjusted by selecting appropriate initiators and reaction conditions. In the preparation process of dental resin, it can ensure that the polymerization reaction is fully carried out to avoid color changes caused by incomplete polymerization or excessive polymerization. At the same time, the controllable polymerization reaction also helps to form a uniform polymer network and improve the color uniformity of the material. During the polymerization process, the polymer formed by these two substances has a low shrinkage rate. Low shrinkage can reduce the internal stress caused by material shrinkage and avoid color changes and unevenness caused by stress. In addition, low shrinkage can also improve the fit between the material and the teeth and reduce marginal leakage, thereby further ensuring the uniform color of the restored teeth. These two substances have good chemical stability and thermal stability. In the oral environment, they can resist erosion by saliva, food, etc. and are not prone to color changes. At the same time, they can also maintain stable physical and chemical properties in the case of changes in oral temperature to ensure long-term color stability.
[0077] In some embodiments of the present invention, in the dental resin mixture, the mass ratio between triethylene glycol dimethacrylate and urethane dimethacrylate is, for example, (1-3): (6-10), (1-3): (7-10), (1-3): (8-10), (1-3): (9-10), (2-4): (6-10), (2-3): (6-9). The two substances in different proportions have different scattering and absorption characteristics for light. Urethane dimethacrylate usually has a higher refractive index and may produce stronger scattering and absorption of light. If its ratio is too high, it may cause the transparency of the material to be reduced and the color to be uneven. The refractive index of triethylene glycol dimethacrylate is relatively low, and it can adjust the scattering and absorption degree of the material to light in an appropriate ratio. Within this mass ratio range, the two substances work together to enable the material to reach a relatively balanced state of scattering and absorption of light, thereby improving the transparency and color uniformity of the material. The color stability of dental resin is closely related to the chemical structure and degree of polymerization of the material. Within this specific mass ratio range, the polymer structure formed after the polymerization of the two substances is relatively stable and is not easily affected by external factors (such as light, oxidation, etc.) and does not change color.
[0078] In some embodiments of the present invention, the initiator is a peroxide and / or an azo compound. These two types of initiators can be distributed more evenly in the resin system and decompose to produce free radicals, so that the polymerization reaction is carried out more evenly in the whole system. Uniform polymerization can ensure that each part of the resin has similar chemical structure and physical properties, thereby making the color of the material more uniform. If the initiator is unevenly distributed, it will lead to different local polymerization speeds, resulting in inconsistent internal structure of the material and causing color difference. During the use of dental resin, the material may be affected by temperature changes in the oral cavity. After initiating polymerization, peroxides and azo compounds can form a polymer network with a certain thermal stability. This thermal stability can reduce the structural changes and color changes of the material caused by temperature changes, and ensure the color uniformity and stability of the dental resin in the oral environment. The materials after the polymerization initiated by these two types of initiators usually have good chemical stability and can resist the erosion of saliva, food, etc. in the oral cavity. Thereby, the material can be prevented from changing color due to the action of chemical substances, ensuring that the dental resin always maintains a small color difference and uniform color during use.
[0079] In some embodiments of the present invention, the mass ratio of peroxide to azo compound is (0-10):(10-0).
[0080] In some embodiments of the present invention, the inorganic particles are 80 to 88 parts by weight, the polymerizable monomer is 12 to 20 parts by weight, and the initiator is 0.0001 to 0.002 parts by weight. The filler weight ratio in this range can form a relatively compact particle filling structure, increasing the overall strength and hardness of the material. In the oral environment, it can withstand chewing pressure and friction, and extend the service life of the dental restoration. In addition, the inorganic particles in this ratio range will not hinder the propagation of light too much, ensuring that the material has a certain degree of transparency and avoiding the phenomenon of being too turbid. The monomers in this ratio can fully wrap and connect the inorganic particles to ensure the integrity and stability of the material. If the monomer ratio is too low, the inorganic particles may not be completely wrapped, resulting in a loose material structure and reduced performance; while if the monomer ratio is too high, the material may become too soft and the mechanical properties may be reduced. This trace amount of initiator can start the polymerization reaction within an appropriate time, and will not cause the reaction to be too violent due to excessive dosage, generate too much heat and internal stress, and affect the performance and color uniformity of the material. However, if the dosage is too small, the polymerization reaction will be too slow or even fail to proceed completely, resulting in incomplete curing of the material and poor performance. Therefore, the present invention provides the above dosage ratio to obtain better performance.
[0081] Exemplarily, the weight parts of inorganic particles can be 83, 85, or 86, the weight parts of polymerizable monomers can be 15, 16, or 18, and the weight parts of initiators can be any one of 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.0010, 0.0012, 0.0015, 0.0017, or 0.0019, or a range consisting of any two values.
[0082] In some embodiments of the present invention, the inorganic particles are selected from at least one of glass, glass ceramics, quartz, fused quartz, silica gel, silicon, aluminum oxide, diatomaceous earth, kaolin, clay minerals, activated soil, natural zeolite, synthetic zeolite, mica, silicon dioxide, calcium fluoride, ytterbium fluoride, calcium phosphate, barium sulfate, zirconium oxide, titanium dioxide, hydroxyapatite and inorganic fillers containing heavy metal elements. Glass, fused quartz, silicon dioxide and the like have good transparency, which can make the dental resin present a natural appearance after curing, which is similar to the color and transparency of natural teeth. Some substances such as titanium dioxide can be used as white pigments to adjust the color of dental resins to make them whiter and more beautiful. At the same time, by controlling the ratio and particle size of these inorganic particles, the color and transparency of the material can be accurately adjusted to meet the needs of different patients. Materials such as quartz and glass ceramics can appropriately reflect and scatter light, so that the dental resin can present a more uniform appearance at different angles. Inorganic particles with high hardness and strength, such as alumina and zirconium oxide, can significantly enhance the mechanical properties of dental resins. Clay minerals such as diatomaceous earth and kaolin can also increase the strength of the material to a certain extent. Some inorganic particles, such as silica gel and silicon, have a low thermal expansion coefficient, which can reduce the shrinkage of dental resins during polymerization. Hydroxyapatite is one of the main components of human bones and teeth and has good biocompatibility. Adding it as an inorganic particle to dental resins can promote the regeneration and repair of tooth tissues and better integrate with surrounding tooth tissues. Substances such as calcium phosphate also have similar biocompatibility and can gradually dissolve and release calcium and phosphorus ions in the oral environment, promote tooth remineralization, and prevent the occurrence of caries. Some inorganic particles, such as natural zeolites and synthetic zeolites, have microporous structures that can adsorb and release antibacterial ions, such as silver ions and zinc ions, and have certain antibacterial and antifouling properties. Calcium fluoride and ytterbium fluoride containing fluorine can release fluoride ions to prevent tooth decay; inorganic fillers containing heavy metal elements can be used to block X-rays, making it easier for doctors to observe the position and status of restorations during diagnosis. Kaolin and clay minerals are abundant in nature and are easy to mine and process, which reduces the production cost of dental resins and ensures a stable supply of materials.
[0083] In some embodiments of the present invention, the glass or glass ceramic contains silicon dioxide as a main component and contains at least one of boron, aluminum or heavy metal elements. Silicon dioxide has high transparency and low refractive index, which can make the dental resin present a natural appearance after curing, similar to the color and transparency of natural teeth. Boron can improve the chemical stability and thermal expansion coefficient of glass. It can enhance the corrosion resistance of glass, making it less susceptible to erosion by saliva, food, etc. in the oral environment, thereby maintaining the color and performance stability of the restoration. Aluminum can increase the hardness and strength of glass. It combines with silicon dioxide to form a more solid structure, further enhancing the mechanical properties of dental resin. Heavy metal elements (within a safe range) can give glass special properties, such as increasing X-ray radiopacity, making it easier for doctors to observe the position and state of the restoration during diagnosis.
[0084] In some embodiments of the present invention, the heavy metal element is at least one of zirconium, barium, titanium, lanthanum or strontium. Glass containing these specific heavy metal elements can significantly improve the hardness and strength of dental resin, reduce the wear rate and have good chemical stability and biocompatibility. In addition, the color and transparency can also be adjusted. For example, glass containing titanium can adjust the color of dental resin, and glass containing lanthanum can increase the transparency of the material.
[0085] In some embodiments of the present invention, the clay mineral is montmorillonite. In dental resin, montmorillonite can absorb some harmful substances in the oral cavity, such as bacterial metabolites, acidic substances, etc., thereby reducing the erosion of teeth and restorative materials. This helps to maintain the stability of the oral environment around the restoration and reduce the risk of caries and inflammation. Montmorillonite has high chemical stability and is not easily corroded by chemicals such as acids and alkalis in the oral environment. This can ensure that the dental resin will not change color or degrade in performance due to chemical corrosion during long-term use. In addition, montmorillonite can also interact with other components in the dental resin to enhance the overall stability of the material.
[0086] In some embodiments of the present invention, the inorganic particles are barium glass powder, preferably silanized barium glass powder. Barium glass powder itself has high hardness and strength, and can significantly enhance the mechanical properties of dental resin. Silanization treatment can improve the interface bonding between barium glass powder and dental resin, reduce light scattering, and make the restoration have better transparency and color stability. Silanized barium glass powder can be better integrated with the resin, making the repaired teeth more natural and beautiful, and reducing color difference. Barium glass powder usually has good biocompatibility. After silanization treatment, it is more stable in combination with human tissue and is not easy to cause allergic reactions or inflammation. The specific composition is barium glass powder wrapped in silane coupling agent, and the elements contained are C, H, O, Si, Ba and some trace metal elements, and the element proportion is the common element proportion of silanized barium glass powder on the market.
[0087] In some embodiments of the present invention, the raw material of the dental resin further includes a colorant, and the colorant is at least one of an organic pigment and an inorganic pigment.
[0088] In some embodiments of the present invention, the organic pigment is selected from at least one of phthalocyanine pigments, quinacridone pigments, perylene pigments, dioxazine pigments, isoindolinone pigments, and anthraquinone pigments.
[0089] In some embodiments of the present invention, the inorganic pigment is an oxide pigment, more preferably at least one of red iron oxide, yellow iron oxide, black iron oxide, and titanium dioxide. These four pigments can provide a rich selection of colors to meet different restoration needs; they can show good stability in the oral environment, are not easily affected by factors such as saliva, food, and bacteria, can maintain color stability for a long time, and reduce the frequency of replacement of restorations due to color changes; they have good biocompatibility and will not cause adverse stimulation or toxic reactions to human tissues. When in contact with teeth and gum tissues, they can ensure the oral health of patients and reduce the occurrence of allergies, inflammation and other problems; they have good compatibility with dental resins and can be evenly dispersed in the resin to ensure color uniformity and stability.
[0090] In some embodiments of the present invention, the colorant is 0 to 1 part by weight; illustratively, it can be any one of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or a range consisting of any two parts.
[0091] Preferably, in the dental resin mixture, the total amount of the inorganic particles, the polymerizable monomer, the initiator and the colorant is 100 parts by weight in each case.
[0092] In some embodiments of the present invention, the polymerizable monomer also includes at least one of bisphenol A propylene glycol dimethacrylate, ethoxylated bisphenol A diacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, methacrylate, polyurethane diacrylate, 2-hydroxyethyl acrylate, and 2-hydroxyethyl methacrylate. These polymerizable monomers can provide good strength and rigidity for dental resins, such as bisphenol A propylene glycol dimethacrylate and ethoxylated bisphenol A diacrylate, to ensure that the restoration is not easily deformed or cracked when subjected to external forces such as chewing force, thereby ensuring the long-term stability and functionality of the restoration. At the same time, ethylene glycol diacrylate, ethylene glycol dimethacrylate, triethylene glycol diacrylate, and triethylene glycol dimethacrylate can impart certain flexibility and elasticity, so that the restoration can adapt to slight deformations of teeth, reduce stress concentration, and reduce the risk of cracking. The polymerizable polymer containing bisphenol A structure has good chemical stability, is not easily corroded by saliva, acid and alkali and other substances in the oral environment, can maintain the stable performance of the restoration, avoid color change and degradation, and extend the service life of the restoration. Some polymerizable polymers have a low shrinkage rate during the polymerization process, such as ethoxybisphenol A diacrylate, which can reduce the formation of gaps between the restoration and the teeth, improve edge sealing, reduce the possibility of bacterial growth and caries, and improve the quality of restoration. Polymerizable polymers related to ethylene glycol and triethylene glycol have good solubility and can be fully mixed with other ingredients to ensure that additives such as pigments and initiators are evenly dispersed in the resin, thereby improving the color uniformity and performance stability of the restoration. Preferably, the total amount of triethylene glycol dimethacrylate and urethane dimethacrylate accounts for at least 50% by weight of the total amount of polymerizable monomers, preferably at least 80% by weight.
[0093] In some embodiments of the present invention, the polymerizable monomer comprises triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of 3:7.
[0094] In some embodiments of the present invention, the initiator is benzoyl peroxide. The dental resin obtained by initiating polymerization with benzoyl peroxide usually has good mechanical properties, such as strength, hardness and wear resistance, can maintain a stable structure in the oral cavity, and is not easily damaged during long-term use. After initiating polymerization, benzoyl peroxide generally does not have an adverse effect on the color of the dental resin. On the contrary, it can promote uniform polymerization of polymerizable monomers, so that the resin has good color stability, high color matching with surrounding teeth, and ensures the aesthetic effect after repair. Under appropriate conditions of use, the dental resin initiated by benzoyl peroxide has good biocompatibility and does not produce irritation or toxic reactions to oral tissues.
[0095] In some embodiments of the present invention, the dental resin mixture further comprises a solvent. The solvent is selected from ethanol, anhydrous ethanol, methanol, propanol, n-propanol, isopropanol, butanol, n-butanol, tert-butanol, isobutanol, amyl alcohol, hexanol, ethylene glycol, propylene glycol, butanediol, glycerol, trimethylolpropane, ethyl acetate, methyl acetate, dimethylformamide, ether, acetone, methyl ethyl ketone, heptane, preferably anhydrous ethanol. The amount of the solvent used is 200-300 parts by weight, based on 100 parts by weight of the total amount of the inorganic particles, the polymerizable monomer, the initiator and the colorant.
[0096] Second aspect
[0097] The present invention provides a dental resin, the raw material of which is the dental resin mixture.
[0098] Preferably, the color of the dental resin is evenly distributed.
[0099] Preferably, the dental resin has a color difference of less than or equal to 1.2 inside.
[0100] The third aspect
[0101] The invention provides a method for preparing a dental resin, comprising the following steps: S1, mixing inorganic particles, a polymerizable monomer, an initiator, an optional solvent and an optional colorant; S2, drying, grinding and sieving the mixture obtained in step S1 to obtain a powdery mixture; S3, dry-pressing the powdery mixture obtained in step S2 to obtain a block blank; S4, heating and pressurizing the block blank obtained in step S3 to harden it, and cooling it to obtain the dental resin.
[0102] In some embodiments of the present invention, in step S1, a ball mill is used for mixing.
[0103] In some embodiments of the present invention, the ball mill jar of the ball mill is made of any one of zirconium oxide, polyurethane, nylon and polyethylene.
[0104] In some embodiments of the present invention, the grinding balls in the ball mill are made of agate or zirconium oxide.
[0105] In some embodiments of the present invention, the rotation speed of the ball mill is 600-800 rpm, and the ball milling time is 0.5-1.5 h. Exemplarily, the rotation speed may be 650 rpm, 700 rpm or 800 rpm; the ball milling time may be 0.8 h, 1 h or 1.2 h. The rotation speed in this parameter range can ensure uniform mixing while avoiding excessive heating. During the grinding process of dental resin materials, overheating may cause chemical changes or performance degradation of the materials. The ball milling time of 0.5-1.5 h can ensure that the dental resin material is fully mixed in the ball mill. Within this time range, various components such as inorganic particles, polymerizable monomers, initiators, etc. can fully contact and collide to achieve uniform mixing.
[0106] In some embodiments of the present invention, a solvent, preferably anhydrous ethanol, is added before ball milling.
[0107] In some embodiments of the present invention, in step S2, a drying oven is used for the drying, and the drying temperature is 45 to 65°C, and the drying time is 4 to 12 hours. Exemplarily, the drying temperature may be 50°C, 55°C or 60°C; the drying time is 6 hours, 8 hours or 10 hours. For dental resin materials, too high a temperature may cause thermal decomposition, oxidation or other chemical changes in the material, thereby destroying the performance of the material. Within this temperature range, relatively low temperatures can avoid serious damage to the chemical structure of the material. This temperature range can effectively remove the solvent in the dental resin material without causing excessive drying or agglomeration of the material. This drying time can meet the requirements of solvent removal without being too long to extend the production cycle. In some embodiments of the present invention, a screen is used for the screening.
[0108] In some embodiments of the present invention, the screen is a synthetic fiber screen or a polyurethane screen. Both the synthetic fiber screen and the polyurethane screen have excellent wear resistance and corrosion resistance. During the screening process of dental resin materials, they can resist the friction, impact of particles and the erosion of chemical substances that may be exposed. The good elasticity and flexibility of the synthetic fiber screen and the certain toughness of the polyurethane screen enable them to adapt to particles of different shapes and sizes, reduce the possibility of particles clogging the screen, help improve screening efficiency, and also facilitate cleaning and maintenance. The screen used in the present invention, if divided by the material system, the screen is a non-metallic material system; if divided by the structural system, the screen is a woven screen system.
[0109] In some embodiments of the present invention, the size of the sieve is 12 to 24 meshes, for example, 18 meshes, 20 meshes, and 22 meshes. The mesh number of the sieve refers to the number of mesh holes within a length of one inch (25.4 mm). For example, a 12-mesh sieve means that there are 12 mesh holes within a length of one inch. A 12-24 mesh sieve can screen out particles of moderate size, which will not be too large to affect the uniformity and processing performance of the material, nor too small to cause the material to be too delicate and lose a certain mechanical strength.
[0110] In some embodiments of the present invention, in step S3, the pressure of the dry pressing is 6-15 MPa, for example, 8 MPa, 10 MPa or 12 MPa. The pressure of 6-15 MPa can fully compact the inorganic particles, polymerizable monomers and other components and reduce the gaps between the particles.
[0111] In some embodiments of the present invention, in the step S4, the block blank is heated and pressurized at a temperature of 90 to 160° C. and a pressure of 120 to 180 MPa for 5 to 8 hours, and the dental resin is obtained after cooling. Within this temperature range, the polymerizable monomers in the dental resin material can more effectively undergo polymerization reactions. Too high a temperature may cause the dental resin material to undergo overheating and decomposition, destroying its chemical structure and reducing the performance of the material. High pressure can make the dental resin material more tightly combined during the heating process, improve the density and strength of the material, eliminate pores and defects in the material, and improve the quality and reliability of the material. Pressure can promote the progress of chemical reactions, and work synergistically with temperature to accelerate the polymerization reaction of the dental resin. Under high pressure, the distance between molecules decreases, the reaction activity increases, and the reaction rate is accelerated. The duration of 5 to 8 hours can give enough time for the monomers to fully polymerize and form a stable polymer structure. If the time is too short, the reaction may not be complete, resulting in incomplete polymerization of the material and unstable performance. For example, the heating temperature may be 120° C. or 150° C., the pressurizing pressure may be 150 MPa or 165 MPa, and the duration may be 6 h or 7 h.
[0112] The fourth aspect
[0113] The present invention provides an evaluation method for evaluating the color difference uniformity of the above-mentioned dental resin, and the evaluation method comprises the following steps: A1, taking at least two samples on the dental resin, using a spectrophotometer, and measuring the L value, a value, and b value of the sample according to the CIELAB color space model, wherein each sample is marked with a number from 1 to n, n is an integer greater than or equal to 2, L1, a1 and b1 are measured for sample No. 1, L1, a1 and b1 are measured for sample No. n, and L n 、a n and b n; A2, substitute the L value, a value, and b value data obtained in step A1 into the formula ΔE (i,j) =[(ΔL (i,j) ) 2 +(Δa (i,j) ) 2 +(Δb (i,j) ) 2 ] 1 / 2 The calculation is performed in which ΔL (i,j) , Δa (i,j) , Δb (i,j) It is the difference between the CIE L, a, and b values of any two samples, that is, ΔL (i,j) =|L i -L j |, Δa (i,j) =|a i -a j |,Δb (i,j) =|b i -b j |, i and j are both integers greater than 0 and not greater than n, i≠j, i represents sample number i, j represents sample number j, ΔE (i,j) represents the color difference between any two samples, where if for any set of i and j, ΔE (i,j) ≤1.2, the color distribution of the dental resin is considered to be uniform.
[0114] It is worth mentioning that in the CLE LAB color system, "L" stands for luminance, which reflects the brightness of the color, that is, the change from black to white; "a" represents the color range from green to red, which mainly reflects the color bias on the red-green axis; "b" represents the color range from blue to yellow, which mainly reflects the color bias on the blue-yellow axis. In dental clinics, the tooth color of different patients is different. The above-mentioned L value, a value, and b value represent the brightness, red-green color, and yellow-blue color of the teeth (or dental resin, or dental restoration), respectively. These three values together determine the color tone of teeth, dental resins, and dental restorations.
[0115] Exemplarily, in some embodiments of the present invention, ΔE (i,j) It can be any one of 1.15, 1.1, 1.05, 1.0, 0.95, 0.9, 0.85, 0.8, 0.75, 0.7, 0.65, 0.6, 0.55, 0.5, 0.45, 0.4, 0.35, 0.3, 0.25, 0.2, 0.15, 0.1, and 0.05, or a range consisting of any two of the above values; it can also be a value smaller than any one of the above values, or a range consisting of any two of the above values.
[0116] In some embodiments of the present invention, in step A1, the center position of the surface of the dental resin is used as the origin to divide the quadrants into four equal parts, and at least one sample is sampled in each quadrant, and n≥4. Exemplarily, n can be 5, 6, 7, 8, 9, 10, 11, 12, 13, etc.; obviously, multiple samples can be taken in the same quadrant. Preferably, n=4, that is, one sample is taken in each quadrant.
[0117] It is worth noting that in the sampling process of this evaluation method, the distance between each sampling point should be as far as possible, so as to be able to more objectively and reliably confirm and evaluate the color uniformity of dental resin; that is, the sampling points should be avoided as much as possible to avoid being too close to each other, which would lead to unreliable sampling data.
[0118] In some embodiments of the present invention, the size of the sample is (1-10)×(1-10)×(1-2) mm. For example, the size of the sample may be 1×1×1 mm, 2×5×1.2 mm, or 6×3×1.8 mm, etc.
[0119] In some embodiments of the present invention, the evaluation method is used to evaluate the color difference uniformity of the dental resin or the dental resin obtained by the above-mentioned preparation method.
[0120] In some embodiments of the present invention, the CIELAB color space model corresponds to the ISO11664-4 standard.
[0121] In some embodiments of the present invention, the L value ranges from 55 to 82, the a value ranges from -2 to 6, and the b value ranges from 2 to 36. In dental clinics, different patients have different tooth colors, and this value range can meet the restoration needs of most patients. The L value represents lightness, which represents the brightness of the restoration; the a value and the b value represent the red-green color and the yellow-blue color, respectively, which together determine the hue of the restoration.
[0122] Fifth Aspect
[0123] The present invention also provides a dental restoration, which is any one of an inlay, an onlay, a crown, a bridge, a veneer, and an implant superstructure; the dental restoration is obtained by cutting with a CAD / CAM device using the above-mentioned dental resin mixture, or the above-mentioned dental resin, or the dental resin obtained by the above-mentioned preparation method.
[0124] Example 1
[0125] A method for preparing a dental resin, the specific steps are as follows:
[0126] S1, weighing 80 g of urethane dimethacrylate, 20 g of triethylene glycol methacrylate and 0.2 g of benzoyl peroxide;
[0127] S2, using an ultrasonic machine, at a frequency of 40 kHz, ultrasonically treating the monomers and initiator for 30 minutes to mix them evenly, to obtain an acrylic monomer resin mixture containing an initiator;
[0128] S3, weighing 8.8 g of barium silanized glass powder with a particle size of 2 μm, 0.0015 g of red iron oxide, 0.0072 g of yellow iron oxide, 0.0013 g of black iron oxide and 1.2 g of the monomer resin mixture obtained in the above step S2, adding them into a nylon ball mill, then adding 30 ml of anhydrous ethanol, and ball milling at a speed of 800 rpm for 0.5 h to obtain a slurry mixture containing an inorganic filler and a resin monomer;
[0129] S4, placing the slurry obtained in step S3 in an oven at 50° C. for 6 hours and then taking it out, grinding it and passing it through a 12-mesh sieve to obtain a powder mixture with fine size and uniform particle size distribution;
[0130] S5, dry-pressing the powdery mixture under a pressure of 10 MPa to obtain a block body;
[0131] S6, sealing the blank with a vacuum sealer and then placing it in a warm isostatic press, polymerizing it at 90° C. and 120 MPa for 6 hours to obtain a dental resin.
[0132] It is worth noting that the silanized barium glass powder used in the embodiment of the present invention is commercially available barium glass powder that has been silanized, and the silane coupling agent used is KH570.
[0133] Example 2
[0134] The only difference between this embodiment and embodiment 1 is that the mass of urethane dimethacrylate weighed in this embodiment is 75 g, the mass of urethane dimethacrylate is 25 g, the mass of the monomer resin mixture is 2 g, the mass of barium glass powder with a particle size of 0.15 μm is 8 g, the mass of red iron oxide is 0.0120 g, the mass of yellow iron oxide is 0.0300 g, the mass of black iron oxide is 0.0080 g, and the mesh size of the sieve used is 16 meshes.
[0135] Example 3
[0136] The only difference between this embodiment and embodiment 1 is that the mass of urethane dimethacrylate weighed in this embodiment is 60 g, the mass of urethane dimethacrylate is 40 g, the mass of the monomer resin mixture is 1.5 g, the mass of barium glass powder with a particle size of 4 μm is 8.5 g, the mass of red iron oxide is 0.0250 g, the mass of yellow iron oxide is 0.0640 g, the mass of black iron oxide is 0.0011 g, and the mesh size of the sieve used is 20 meshes.
[0137] Example 4
[0138] The only difference between this embodiment and embodiment 1 is that the mass of urethane dimethacrylate weighed in this embodiment is 65 g, the mass of urethane dimethacrylate is 35 g, the mass of the monomer resin mixture is 1.7 g, the mass of barium glass powder with a particle size of 2 μm is 8.3 g, the mass of red iron oxide is 0.0110 g, the mass of yellow iron oxide is 0.0142 g, the mass of black iron oxide is 0.0048 g, and the mesh size of the sieve used is 22 meshes.
[0139] Example 5
[0140] The only difference between this embodiment and embodiment 1 is that the mass of urethane dimethacrylate weighed in this embodiment is 70 g, the mass of urethane dimethacrylate is 30 g, the particle size of barium silanate glass powder is 0.7 μm, the mass of red iron oxide is 0.0436 g, the mass of yellow iron oxide is 0.0264 g, the mass of black iron oxide is 0.0100 g, and the mesh size of the sieve used is 24 meshes.
[0141] Example 6
[0142] The difference between this example and Example 1 is that ethylene glycol dimethacrylate is used in this comparative example instead of triethylene glycol methacrylate.
[0143] Example 7
[0144] The difference between this example and Example 1 is that triethylene glycol dimethacrylate is used in this comparative example instead of triethylene glycol methacrylate.
[0145] Example 8
[0146] The difference between this example and Example 1 is that bisphenol A propylene glycol dimethacrylate is used in this comparative example instead of urethane dimethacrylate.
[0147] Example 9
[0148] The difference between this example and Example 1 is that polyurethane diacrylate is used in this comparative example instead of urethane dimethacrylate.
[0149] Example 10
[0150] The difference between this example and Example 1 is that this comparative example uses triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of 1:1.
[0151] Embodiment 11
[0152] The difference between this example and Example 1 is that this comparative example uses triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of 1:12.
[0153] Example 12
[0154] The difference between this embodiment and embodiment 1 is that this comparative example uses barium silanization glass powder with a particle size of 20 μm.
[0155] Example 13
[0156] The difference between this embodiment and embodiment 1 is that this comparative example uses barium silanization glass powder with a particle size of 0.05 μm.
[0157] Comparative Example 1
[0158] The difference between this comparative example and Example 1 is that in this example, 0.0012 g of red iron oxide, 0.0058 g of yellow iron oxide, and 0.0010 g of black iron oxide are used, and the dried curable composition is not ground or sieved but directly dry-pressed.
[0159] Comparative Example 2
[0160] The difference between this comparative example and Example 1 is that in this example, 0.0023 g of red iron oxide, 0.0108 g of yellow iron oxide, and 0.0020 g of black iron oxide are used, and the inorganic filler composition and the inorganic monomer composition are stirred and mixed under heating conditions without using a solvent for dilution.
[0161] Comparative Example 3
[0162] The difference between this comparative example and Example 1 is that this example uses barium glass powder, which is not subjected to silanization treatment.
[0163] Test Example 1
[0164] In this test example, the above evaluation method was used to test the color difference of the dental resin obtained in the above embodiment and comparative example. The dental resin obtained in each embodiment and comparative example was divided into four quadrants, and a sample was taken from each quadrant for detection using a spectrophotometer. The test results are shown in Table 1 below.
[0165] Table 1 L value, a value and b value of each embodiment and comparative example
[0166]
[0167]
[0168] Using the color difference evaluation method provided by the present invention, the L value, a value and b value in Table 1 are substituted into the above formula for calculation. The calculation results are shown in Table 2 below, where the color difference between sample 1 and sample 2 is ΔE 1-2 , and so on.
[0169] Table 2 ΔE between two samples in each embodiment and comparative example
[0170]
[0171]
[0172] As can be seen from Table 2, the dental resins obtained in Examples 1-13 of the present invention have a lower color difference value, ΔE is between 0.06-1.19, and the color uniformity of Example 5 is the best. In terms of resin ratio, the polymer network structure formed by the ratio of urethane dimethacrylate and triethylene glycol methacrylate in the polymerization reaction is more optimized, which can better disperse stress, improve mechanical properties, adapt to the complex force environment of the oral cavity, and reduce the risk of breakage and damage. The barium silanized glass powder with a particle size of 0.7 μm is more evenly dispersed in the resin, and more filler particles are in close contact with the resin matrix to form a firm interface bond, thereby improving the strength and hardness of the resin. At the same time, small-particle fillers can also fill microscopic pores and defects in the resin, increase the density of the resin, reduce the possibility of bacterial invasion and corrosion, and improve biocompatibility and durability. The mesh size of the sieve is 24 meshes, which can screen out a powdery mixture with a finer and more uniform particle size distribution. This makes the resin particle size more consistent, reduces performance differences, improves mechanical properties and optical properties, and makes dental restorations more beautiful and durable. At the same time, the removal of larger particles and impurities improves the purity and quality of the resin, which is conducive to the formation of a uniform structure during the polymerization reaction, reduces the generation of defects, and enhances the performance and reliability of the dental resin.
[0173] Test Example 2
[0174] This test example tests the bending strength and Vickers hardness of the dental resin obtained in the above examples 1-13 and comparative examples 1-3; a universal testing machine (AGS, Shimadzu, Japan) is used to test the bending strength, and a three-point bending test is used to test the Vickers hardness, with a loading rate of 1 mm / min and a sample size of 16×4×2 mm; a Vickers hardness tester (VH1150, Wilson, USA) is used to test the hardness, and the sample size is 16×4×2 mm. The test results are shown in Table 3 below.
[0175] Table 3 Bending strength and Vickers hardness of dental resins obtained in various embodiments and comparative examples
[0176] Bending strength / MPa <![CDATA[Hardness / N·mm -2 > Example 1 191.98 86.5 Example 2 196.95 78.6 Example 3 200.28 84.4 Example 4 209.17 95.8 Example 5 228.27 102.4 Example 6 193.41 82.2 Example 7 185.44 86.4 Example 8 189.25 93.8 Example 9 187.03 94.3 Example 10 193.65 92.0 Embodiment 11 187.46 81.2 Example 12 192.74 93.5 Example 13 185.11 79.6 Comparative Example 1 182.33 80.5 Comparative Example 2 166.96 67.2 Comparative Example 3 171.23 78.1
[0177] As shown in Table 3, the resin materials of Examples 1 to 13 of the present invention have relatively high bending strength, ranging from 185 to 228 MPa, and Vickers hardness ranging from 78.6 to 102.4 N·mm. -2 Among them, the bending strength and Vickers hardness of Example 5 are the best, exceeding 220MPa and 100N·mm -2 , which can meet the requirements of oral restoration production. In terms of resin ratio, the polymer network structure formed by the ratio of urethane dimethacrylate and triethylene glycol methacrylate in the polymerization reaction is more optimized, which can better disperse stress, improve mechanical properties, adapt to the complex stress environment of the oral cavity, and reduce the risk of cracking and damage. The barium silanized glass powder with a particle size of 0.7μm is more evenly dispersed in the resin, and more filler particles are in close contact with the resin matrix to form a strong interface bond, thereby improving the strength and hardness of the resin. At the same time, small-particle fillers can also fill microscopic pores and defects in the resin, increase the density of the resin, reduce the possibility of bacterial invasion and corrosion, and improve biocompatibility and durability. The mesh size of the sieve is 24 meshes, which can screen out a powder mixture with finer and more uniform particle size distribution. This makes the resin particle size more consistent, reduces performance differences, improves mechanical properties and optical properties, and makes dental restorations more beautiful and durable. At the same time, removing larger particles and impurities improves the purity and quality of the resin, which is conducive to forming a uniform structure in the polymerization reaction, reducing defects, and enhancing the performance and reliability of dental resins.
[0178] The above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims. In addition, the specification uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. The content of this specification should not be understood as a limitation on the present invention.
Claims
1. A dental resin mixture, characterized in that: The dental resin mixture comprises: Inorganic particles, polymerizable monomers and initiators; The particle size of the inorganic particles is 0.1 to 6 μm, preferably 0.5 to 5 μm, and the polymerizable monomer comprises triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of (1 to 4): (6 to 10), preferably (2 to 4): (6 to 9).
2. The dental resin mixture according to claim 1, characterized in that: The inorganic particles are 80 to 88 parts by weight, preferably 80 to 85 parts by weight, the polymerizable monomer is 12 to 20 parts by weight, preferably 15 to 20 parts by weight, and the initiator is 0.0001 to 0.002 parts by weight, preferably 0.0003 to 0.0016 parts by weight.
3. The dental resin mixture according to claim 1 or 2, characterized in that: The inorganic particles are selected from at least one of glass, glass ceramics, quartz, fused quartz, silica gel, silicon, alumina, diatomaceous earth, kaolin, clay minerals, activated soil, natural zeolite, synthetic zeolite, mica, silicon dioxide, calcium fluoride, ytterbium fluoride, calcium phosphate, barium sulfate, zirconium oxide, titanium dioxide, hydroxyapatite and inorganic fillers containing heavy metal elements; Preferably, the glass or glass ceramic comprises silicon dioxide as a main component and contains at least one of boron, aluminum or heavy metal elements; Preferably, the heavy metal element is selected from at least one of zirconium, barium, titanium, lanthanum or strontium; Preferably, the clay mineral is montmorillonite; Preferably, the inorganic particles are barium glass powder, more preferably silanized barium glass powder.
4. The dental resin mixture according to claim 1 or 2, characterized in that: The dental resin mixture also includes a colorant; The colorant is selected from at least one of organic pigments and inorganic pigments; Preferably, the organic pigment is selected from at least one of phthalocyanine pigments, quinacridone pigments, perylene pigments, dioxazine pigments, isoindolinone pigments, and anthraquinone pigments; Preferably, the inorganic pigment is an oxide pigment, more preferably at least one selected from red iron oxide, yellow iron oxide, black iron oxide, and titanium dioxide; Preferably, the colorant is 0 to 1 part by weight, preferably 0.005 to 0.5 part by weight, based on 100 parts by weight of the sum of the inorganic particles, polymerizable monomers, initiators and colorants in the dental resin mixture.
5. The dental resin mixture according to claim 1 or 2, characterized in that: The polymerizable monomer further comprises at least one of bisphenol A propylene glycol dimethacrylate, ethoxy bisphenol A diacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, triethylene glycol dimethacrylate, methacrylate, polyurethane diacrylate, 2-hydroxyethyl acrylate, and 2-hydroxyethyl methacrylate; Preferably, the total amount of triethylene glycol dimethacrylate and urethane dimethacrylate accounts for at least 50% by weight, preferably at least 80% by weight of the total amount of polymerizable monomers.
6. The dental resin mixture according to claim 1 or 2, characterized in that: The polymerizable monomer includes triethylene glycol dimethacrylate and urethane dimethacrylate in a mass ratio of 3:
7.
7. The dental resin mixture according to claim 1 or 2, characterized in that: The initiator is a peroxide and / or an azo compound. Preferably, the initiator is benzoyl peroxide.
8. The dental resin mixture according to claim 1 or 2, characterized in that: The dental resin mixture further comprises a solvent; The solvent is preferably selected from ethanol, anhydrous ethanol, methanol, propanol, n-propanol, isopropanol, butanol, n-butanol, tert-butanol, isobutanol, pentanol, hexanol, ethylene glycol, propylene glycol, butylene glycol, glycerol, trimethylolpropane, ethyl acetate, methyl acetate, dimethylformamide, ether, acetone, methyl ethyl ketone, heptane, more preferably anhydrous ethanol.
9. A dental resin, characterized in that: The raw material of the dental resin is the dental resin mixture according to any one of claims 1 to 8.
10. A method for preparing the dental resin according to claim 9, characterized in that: The method comprises the following steps: S1, mixing inorganic particles, polymerizable monomers, initiators, optional solvents and optional colorants; S2, drying, grinding, and sieving the mixture obtained in step S1 to obtain a powdery mixture; S3, dry-pressing the powdery mixture obtained in step S2 to obtain a block body; S4, heating and pressurizing the block body obtained in step S3 to harden it, and obtaining the dental resin after cooling.
11. The preparation method according to claim 10, characterized in that: In the step S1, a ball mill is used for the mixing; Preferably, the ball mill jar of the ball mill is made of any one of zirconium oxide, polyurethane, nylon and polyethylene; Preferably, the grinding balls in the ball mill are made of agate or zirconium oxide; Preferably, the rotation speed of the ball mill is 600-800 rpm, and the ball milling time is 0.5-1.5 h; Preferably, a solvent, preferably anhydrous ethanol, is added before ball milling.
12. The preparation method according to claim 10, characterized in that: In step S2, the drying is performed in a drying oven at a temperature of 45 to 65° C. for a drying time of 4 to 12 hours; Using a sieve to perform the screening; Preferably, the screen is a synthetic fiber screen or a polyurethane screen; Preferably, the size of the sieve is 12 to 24 meshes.
13. The preparation method according to claim 10, characterized in that: In the step S3, the pressure of the dry pressing is 6-15 MPa.
14. The preparation method according to claim 10, characterized in that: In the step S4, the block green body is heated and pressurized at a temperature of 90 to 160° C. and a pressure of 120 to 180 MPa for 5 to 8 hours, and then cooled to obtain the dental resin.
15. A method for evaluating the color difference uniformity of the dental resin according to claim 9, characterized in that: The evaluation method The following steps are involved: A1, taking at least two samples on the dental resin, using a spectrophotometer, and measuring the L value, a value, and b value of the samples according to the CIELAB color space model corresponding to ISO11664-4, Each sample is numbered from 1 to n, where n is an integer greater than or equal to 2. Sample No. 1 measures L1, a1, and b1, and sample No. n measures L n 、a n and b n ; A2, substitute the L value, a value, and b value data obtained in step A1 into the formula ΔE (i,j) =[(ΔL (i,j) ) 2 +(Δa (i,j) ) 2 +(Δb (i,j) ) 2 ] 1 / 2 The calculation is performed in which ΔL (i,j) , Δa (i,j) , Δb (i,j) It is the difference between the CIE L, a, and b values of any two samples, that is, ΔL (i,j) =|L i -L j |, Δa (i,j) =|a i -a j |,Δb (i,j) =|b i -b j |, i and j are both integers greater than 0 and not greater than n, i≠j, i represents sample number i, j represents sample number j, ΔE (i,j) Represents the color difference between any two samples. Among them, if for any set of i and j, there is ΔE (i,j) ≤1.2, the color distribution of the dental resin is considered to be uniform.
16. The evaluation method according to claim 15, characterized in that: In the step A1, the center position of the surface of the dental resin is taken as the origin to divide the surface into four equal quadrants, and at least one sample is sampled from each quadrant, where n≥4.
17. The evaluation method according to claim 15, characterized in that: The size of the sample is (1-10)×(1-10)×(1-2) mm.
18. A dental restoration, characterized in that: The dental restoration is any one of an inlay, an onlay, a crown, a bridge, a veneer, and an implant superstructure; The dental restoration is obtained by cutting using a CAD / CAM device using the dental resin mixture according to any one of claims 1 to 8, or the dental resin according to claim 9, or the dental resin obtained by the preparation method according to any one of claims 10 to 14.
Citation Information
Cited By
Dental resin and preparation method therefor, color difference uniformity evaluation method, and dental restoration
WO2026056405A1